1989
DOI: 10.1093/oxfordjournals.humrep.a136877
|View full text |Cite
|
Sign up to set email alerts
|

Culture of epithelial cells derived from the oviduct of different species

Abstract: This study proposes a procedure for the isolation and culture of oviduct epithelial cells of several species. In-vitro culture on such a feeder seems to allow full embryonic development and viability. The inner linings of Fallopian tubes from mouse, rabbit, cow and human were trypsinized and the epithelial cells were enriched with Percoll gradient. Isolated cells, obtained in high yield with good viability, were maintained in monolayer culture in B2-Menezo medium supplemented with serum, which also supports ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 0 publications
6
32
0
Order By: Relevance
“…The success of primary fallopian tube cell culture is in accordance with other workers (7,8). The method described to obtain the primary culture was found to be the most successful of several tried in preliminary studies and in accordance with other methods reported by previous authors (9,10).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The success of primary fallopian tube cell culture is in accordance with other workers (7,8). The method described to obtain the primary culture was found to be the most successful of several tried in preliminary studies and in accordance with other methods reported by previous authors (9,10).…”
Section: Discussionsupporting
confidence: 88%
“…There are conflicting reports in the literature on the ability successfully to passage human tubal epithelial cells over several passages. Henriksen et al (12) reported unsuccessful attempts, whereas Ouhibi et al (7) were successful.…”
Section: Discussionmentioning
confidence: 99%
“…The technical aspects of Vero cells maintenance have been described by Ouhibi et al [9]. Briefly, from the frozen cells, flasks (3013, Falcon, USA) were seeded with 2-3 × 10 6 cells and reached confluence within 4 days (6-8 × 10 6 cells /flask).…”
Section: Preparation Of Vero Cells and Embryo Co-culturementioning
confidence: 99%
“…The culture medium was Medium 199 (11150-059, Gibco, USA) containing 10% fetal bovine serum (FBS, 26140-079, Gibco, USA) and 0.5% antibiotics. The methods for Vero cell freezing and thawing are described by Ouhibi et al [9]. Injected and fertilized oocytes were co-cultured in DMEM supplemented with 20% hFF until transferred.…”
Section: Preparation Of Vero Cells and Embryo Co-culturementioning
confidence: 99%
“…The technical aspects of Vero cell maintenance have been described by Ouhibi et al [10]. Briefly, from the frozen cells, flasks were seeded at 2~3 × 10 6 cells and reached confluency within 4 days (6~8 × 10 6 /flask).…”
Section: Culture Of Vero Cellsmentioning
confidence: 99%